General Provisions and Procedures for Taxation - Avian Rezky Nevianto; Elsa Putri Delpani; Galuh Tresna Murti; Rizki Jodi Sulistyawan (Universitas Muhammadiyah Makassar, 2023)
Taxes are a mandatory contribution to the state. Where taxes are one of the state income. The purpose of writing this article is to provide information about taxation in general and get basic reasoning about the general procedures and provisions of taxation as a useful knowledge base for implementing tax law. Writing is carried out using qualitative methods with sources obtained by means of literature studies. The result of this research is the existence of a system in tax collection, tax rates, principles, arising and elimination of tax debt, as well as obstacles to tax collection. So it is found that in taxation there is a collection system, as well as principles and rates that are adjusted to the tax subject and tax object. And there are obstacles in collecting taxes, as well as the causes of the emergence and elimination of taxes.